Poverty-related diseases (PRDs): unravelling complexities in disease responses in Cameroon. Issue 1 (December 2017) - Makoge, Valerie; Maat, Harro; Vaandrager, Lenneke; Koelen, Maria
Abstract Background In Cameroon, poverty-related diseases (PRDs) are a major public health concern. Research and policies addressing PRDs are based on a particular understanding of the interaction between poverty and disease, usually an association between poverty indicators and health indicators for a specific country or region. Such indicators are useful but fail to explain the nature of the linkages between poverty and disease or poverty and health. This paper presents results of a study among university students, unravelling how they perceive diseases, the linkages with poverty, their responses to diseases and the motivations behind reported responses. Based on the health belief model, this cross-sectional study was carried out among 272 students at the universities of Buea and Yaoundé in Cameroon. Data were collected using questionnaires containing items matching the research objectives. The questionnaires were self-completed. Results Malaria was considered as the most common disease perceived and also a major PRD. Contrary to official rankings of HIV/AIDS and TB, cholera and diarrhoea were considered as other major PRDs. Also, typhoid fever was perceived to be more common and a PRD than HIV/AIDS and TB combined. The most prominently attributed cause for disease was (lack of) hygiene. In response, students deployed formal and/or informal healthcare strategies, depending on factors like available money, perceived severity of the disease and disease type. Discrepancies were observed in respondents' response to diseases generally and to malaria in particular. Even though, overall, respondents pre-dominantly reported a formal healthcare response toward diseases in general, for malaria, informal responses dominated. There was an overall strong awareness and (pro)activity among students for dealing with diseases. Conclusions Although the high use of informal facilities and medication for malaria may well be a reason why eradication is problematic, this seems to be a deliberate strategy linked to an awareness of the limitations of the formal health system. In any intervention intended to foster health, it is therefore vital to consider people's perceptions toward diseases and their response strategies. Our results give important leads to health promotion interventions to develop group-specific programs.